The importance of physical education teacher Training for children with disabilities in Elementary School - Sousa, Adão Rodrigues de; Guimarães Junior, José Carlos; Santana, Marttem Costa de; Santos, Laurita Christina Bonfim; Silva, Jadilson Marinho da; Silva, Wellynton Rodrigues da; Santos, Jefferson Davi Ferreira dos; Freitas, Daiana Vincunha Lira Freitas; Araújo, Jânio Alexandre de (Research, Society and Development, 2022)
The objective of this article was to verify how physical education contributes to the inclusive development of students with special educational needs. Bearing in mind the widespread misconception that access to education is difficult because people with disabilities are seen as sick and incapable, They have always been at a disadvantage , imagining themselves as recipients of public and charitable assistance, and not as subjects of social rights, which includes the right to education Even today, it can be difficult for people to accept what is different in their social and family context, however, by raising awareness of the issue and expanding the body of literature on this, we can help these individuals integrate into society more effectively. To start promoting the child's development at school, in the family and in society, it is necessary to understand the child's limitations, assess their level of difficulty and rely on the help of qualified professionals. To start promoting the child's development at school, in the family and in society, it is necessary to understand the child's limitations, assess their level of difficulty and work with qualified professionals. The objective was to demonstrate how physical education can serve as a bridge between the disabled child and society, helping the child to overcome obstacles, recognize and develop their abilities, improve their motor repertoire, favor social, cognitive and affective adjustments, as well as raise self-esteem, self-confidence and self-knowledge as a way of overcoming, insertion, health, balance, independence and autonomy. Based on this context, the main objectives of this study were to identify and reflect on the educational actions of the physical education teacher as a factor that influences the inclusion of students with disabilities in physical education classes.